Pre-channel scheduling and Priority-based reservation in medium access control for industrial wireless sensor network applications. (November 2017) - R., Kannan; S., Solai Manohar; M., Senthil Kumaran
Abstract: Numerous technical advancements and the pervasive controlling schemes in the Industrial Wireless Sensor Network (IWSN) with the capability of interoperability among the nodes facilitate the reliable communication. With the increase of participating sensors size, the memory and energy consumption reduce the lifetime adversely. To alleviate these issues, this paper creates an energy efficient data management and routing architecture based on the data fusion techniques in IEEE 802.15.4. The data classification through proposed Multi-Stage Classification (MSC) prior to priority assignment techniques makes the immediate decision regarding the controlling actions. The split up of data using Reservation-based Medium Access Control (RMAC) raises the resource allocation requests according to the data type. The built up of the relationship between the number of slots and the data arrival enhances the resource utilization performance for each slot. The guarantee of transfer of immediate transmission with the priority supports the critical conditions with high energy efficiency.